Improving the Properties of Non G30 Soil for Use as Subbase Material with Tea Production Waste-Lime Blend. - Baluku, Bennet (Kabale University, 2024)
This research examined the potential of enhancing the engineering properties of non-G30 soil from Kabale Municipality for use as subbase material by stabilizing it with a mixture of lime and tea production waste. The study aimed to identify the optimal blend that improves the soil's strength and work-ability while adhering to G30 specifications. Lime was combined with tea waste, an organic by-product of tea processing, to assess its effectiveness in modifying key soil characteristics such as the California Bearing Ratio (CBR), Maximum Dry Density (MDD), Optimum Moisture Content (OMC), Liquid Limit (LL), and Plasticity Index (PI). Various replacement ratios of lime and tea waste were analyzed: 3% (2% lime, 1% tea waste), 5% (3% lime, 2% tea waste), 7% (4% lime, 3% tea waste), 9% (5% lime, 4% tea waste), and 11% (6% lime, 5% tea waste). The results indicated that the optimal stabilization was achieved with a 5% to 7% blend, where the soil met the required CBR, CBR swell, LL, and PI values, making it suitable for subbase use. However, higher amounts of tea waste led to reduced CBR and increased LL, highlighting the importance of balancing the organic content. The study concluded that using a lime-tea waste blend offers a sustainable and cost-effective approach to improving non-G30 soils, particularly in regions like Kabale Municipality, where tea waste is readily available.